2021
DOI: 10.1093/nar/gkab214
|View full text |Cite
|
Sign up to set email alerts
|

The effect of flanking bases on direct and triplet sensitized cyclobutane pyrimidine dimer formation in DNA depends on the dipyrimidine, wavelength and the photosensitizer

Abstract: Cyclobutane pyrimidine dimers (CPDs) are the major products of DNA produced by direct absorption of UV light, and result in C to T mutations linked to human skin cancers. Most recently a new pathway to CPDs in melanocytes has been discovered that has been proposed to arise from a chemisensitized pathway involving a triplet sensitizer that increases mutagenesis by increasing the percentage of C-containing CPDs. To investigate how triplet sensitization may differ from direct UV irradiation, CPD formation was qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 90 publications
8
27
0
Order By: Relevance
“…S3C) were dominated by a T in the second position and by having another pyrimidine as the first base. This pattern is similar to one obtained after in vitro irradiation of DNA with UVB ( 25 ).…”
Section: Resultssupporting
confidence: 86%
“…S3C) were dominated by a T in the second position and by having another pyrimidine as the first base. This pattern is similar to one obtained after in vitro irradiation of DNA with UVB ( 25 ).…”
Section: Resultssupporting
confidence: 86%
“…To further confirm that NFX, TOP and IOP were indeed photosensitizing CPD formation, we carried out high-resolution sequencing gel experiments with a 5 0 -[ 32 P]-end-labeled 42-mer sequence containing the eight possible GPyPyG and APyPyA sites (Figure S4). We found that the major bands induced by UVA + sensitizer + T4-pdg occurred at ATTA and to a much lesser extent at GTTG, and undetectable at C-containing CPD sites in accord with our previous work on flanking sequence effects on photosensitized CPD formation with NFX (34). At the ATTA site, CPDs formed with decreasing efficiency in the order NFX>TOP>IOP with a ratio of 1 > 0.24 > 0.08, respectively.…”
Section: Relative Frequency Of Photosensitizer Induced Cpds and Stran...supporting
confidence: 89%
“…The assay is based on the ability of T4 pyrimidine dimer glycosylase (T4-pdg) to cleave the phosphodiester backbone of DNA at CPDs by a lyase mechanism following cleavage of the glycosidic bond of the 5 0pyrimidine (30,31). T4-pdg can also efficiently cleave abasic sites (32) and formamido-dA (FAPYdA) products ( 33), but a recent study of photosensitization by NFX and acetone using T4pdg only showed cleavage at the 5 0 -pyrimidine of dipyrimidines indicating that photosensitization does not produce significant amounts of these other products (34). To quantify the number of CPDs produced, use was made of the fact that introduction of just one single-strand break in supercoiled circular duplex DNA (Form I) converts it to relaxed open circular DNA (Form II) which has a lower electrophoretic mobility in an agarose gel and can be quantified by imaging of an ethidium bromide-stained gel.…”
Section: T4-pdg Coupled Electrophoresis Assay For Cpd Formationmentioning
confidence: 99%
“…Spectroscopical data of novel compounds were consistent with the expected structures, as well as full comparable with data previously reported for photo-adducts deriving from N-1 methyl thymine and thymidine derivatives [27][28][29][30][31][32][33][34][35][36][37]. Again, CPD-TS isomers prevailed with respect to the CS counterpart (Table 2, entries 4-6) [41][42][43]. As a general trend, the total yield of photo-adducts increased by increasing the carbon length of the spacer.…”
Section: Synthesis Of Cpd (6-4)pp and DV Photo-adducts By Uv-irradiation Of Biomimetic Thymine Dimers 4a-dsupporting
confidence: 86%